Country Revitalization: Japan’s Nation Branding Post 3/11 Disaster Performed in the Tokyo Olympics 2020 - Kiki Widya Febrianti; Hamdan Nafiatur Rosyida (Insignia: Journal of International Relations, 2022)
Abstract In 2011, Japan was hit by a series of major disasters, from an earthquake and tsunami that struck the Fukushima Daiichi Nuclear Power Plant (NPP) reactor. Its incident caused Japan to suffer various damage from the economic, health, and environmental sectors, including the emergence of negative stereotypes at the global level. Therefore, Japan was chosen as the host country of the Tokyo Olympics 2020 sports event, and being used to restore Japan’s image in the international area. This study aims to analyze the forms of Japanese national branding after the 3/11 disaster through the Tokyo Olympics 2020. This study uses a qualitative descriptive method. This study uses the concept of soft power and nation branding according, to Keith Dinnie, related to the stages of nation branding in the form of nation-brand identity, communicators of nation-brand identity, and nation-brand image. The results show that Fukushima as a territory promoted in the Tokyo Olympics through several reconstructed facilities to its natural products and culture. Although Fukushima is starting to show a positive image in the international community, Japan’s national branding still requires several challenges. Keywords: Fukushima nuclear disaster, Japan’s revitalization, nation branding, Tokyo Olympics 2020